Aluminum nitride powder and resin composition
By preparing specific aluminum nitride powders, the problem of difficult to take into account both the thermal conductivity and the fluidity of the aluminum nitride filled resin in the prior art is solved, and a resin composition with high thermal conductivity and good fluidity is achieved.
Patent Information
- Application Number
- CN202380060373.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, although aluminum nitride is filled into the resin, it is difficult to maintain high thermal conductivity and good fluidity at the same time, and the relationship between the surface state and thermal conductivity of aluminum nitride particles has not been studied in detail.
By preparing a specific aluminum nitride powder, the particle ratio in the range of 5 to 150 μm is 60 volume % or more in the volume reference particle size distribution, and in the frequency distribution curve, the range of 5 to 50 μm and the range of 50 to 150 μm respectively have peaks, and more than 50% of the particles in the range of 5 to 50 μm are multi-faceted particles.
When forming a resin composition in the resin, the combination of high thermal conductivity and good fluidity is achieved, and the performance of the heat dissipation component is improved.
Smart Images

Figure CN119731118A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to aluminum nitride powder and a resin composition containing the aluminum nitride powder. Background Art
[0002] As electronic devices become more advanced in performance, semiconductor elements are increasingly being mounted at higher densities. At the same time, it is important to more effectively release heat from electronic components that constitute electronic devices. For example, thermal interface materials are used in semiconductor devices to effectively release heat generated by electronic components. Thermal interface materials are materials used to reduce the thermal resistance of the path for heat generated by semiconductor elements to escape to a heat sink or housing, and are used in a variety of forms such as sheets, gels, and greases. As a thermal interface material, a heat dissipation material obtained by filling a resin such as an epoxy resin or a silicone resin with a thermally conductive filler such as aluminum nitride is known.
[0003] When a thermally conductive filler such as aluminum nitride is filled into a resin, since the thermal conductivity of the resin itself is low, a method of improving the thermal conductivity by combining a plurality of aluminum nitrides having different average particle sizes is known in order to increase the filling rate of the thermally conductive filler or to facilitate the formation of a heat path.
[0004] Patent Document 1 discloses an invention regarding aluminum nitride powder, wherein the average particle size D of the aluminum nitride powder is 50 The particle size is 15 to 200 μm, the content of particles with a particle size of less than 5 μm is less than 60% based on the number, the alkaline earth metal, rare earth element, oxygen content and silicon content are low, and it is also recorded that the aluminum nitride powder has excellent filling properties for polymer materials.
[0005] Patent document 2 discloses an aluminum nitride powder as an aluminum nitride powder capable of improving the thermal conductivity of a heat dissipation component, characterized in that the powder has an average particle size of 20 to 50 μm, an oxygen content of 0.6% by mass or less, and an average half-value width of diffraction peaks of three Miller index planes, namely, (100), (002) and (101), obtained by X-ray diffraction, of less than 0.095°.
[0006] Non-patent document 1 describes the average particle size (D 50 ) was aluminum nitride powder with a diameter of 60 μm, and its filling property into resin, thermal conductivity, water resistance, etc. were studied, and it was recorded that their various physical properties were good. Prior art literature Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 216591 Patent Document 2: Japanese Patent Application Publication No. 2003-119010 Non-patent literature
[0008] Non-patent document 1: "Development of large-particle aluminum nitride filler by combustion synthesis", Polymer, Vol. 70, June, 308-309 (2021) Summary of the invention Problems to be solved by the invention
[0009] By filling the aluminum nitride disclosed in the above-mentioned prior art into a resin, the thermal conductivity is improved to a certain extent, and the heat dissipation is good. However, with the increase in the density of power devices in recent years, higher heat dissipation is required. In addition, in the prior art, there is no detailed study on the relationship between the surface state or particle shape of each particle of aluminum nitride and the thermal conductivity when filled into a resin. Furthermore, if the filling rate of aluminum nitride in the resin is increased in order to improve the thermal conductivity, the fluidity of the resin composition itself will be reduced or the handling property will be deteriorated. In other words, improving the thermal conductivity of the resin composition and maintaining good fluidity are usually contradictory. An object of the present invention is to provide an aluminum nitride powder having high thermal conductivity and good fluidity when filled in a resin to form a resin composition. Means of solving problems
[0010] In order to achieve the above-mentioned purpose, the inventors of the present invention have repeatedly conducted in-depth research. As a result, it was found that the above-mentioned problems can be solved by the following aluminum nitride powder, thereby completing the present invention. Specifically, for the aluminum nitride powder, in the volume-based particle size distribution measured by particle size distribution measurement, there are more than 60 volume % of particles in the range of 5 to 150 μm among all particles, and in the frequency distribution curve obtained by the above particle size distribution measurement, specific parameters are met, and more than 50% of the particles with a particle size in a specific range are polyhedral particles with at least 2 flat surfaces.
[0011] The gist of the present invention is the following [1] to [6]. [1] An aluminum nitride powder, wherein: (i) in the volume-based particle size distribution measured by particle size distribution measurement, the proportion of particles in the range of 5 to 150 μm in all particles is 60% by volume or more, (ii) In the frequency distribution curve obtained by the particle size distribution measurement, there are peaks in the particle size range of 5 to 50 μm (M range) and the particle size range of more than 50 μm and 150 μm or less (L range), and the proportion of particles in the M range (M range) is int ) and the ratio of particles in the L range (L int ) ratio (Mint / L int ) is 0.2~1.0, In a scanning electron microscope image taken at a magnification of 500 times, 50% or more of particles having a particle size of 5 to 50 μm are polyhedral particles having at least two flat surfaces. [2] The aluminum nitride powder as described in [1] above, further comprising particles having a particle size of less than 5 μm (S range). [3] The aluminum nitride powder as described in [2] above, wherein the particles having a particle size of less than 5 μm (S range) are aluminum nitride particles and / or aluminum oxide particles. [4] A resin composition comprising the aluminum nitride powder according to any one of [1] to [3] above and a resin. [5] A heat dissipation component comprising the resin composition according to [4] above. [6] An electronic device comprising the heat dissipation component described in [5] above and an electronic device having a heat generating portion or a cooling portion, wherein the heat dissipation component is arranged on the electronic device so as to contact the heat generating portion. Effects of the Invention
[0012] According to the present invention, it is possible to provide an aluminum nitride powder having high thermal conductivity and good fluidity when filled in a resin to form a resin composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] [ Figure 1 ] is a scanning electron microscope image taken at a magnification of 500 times of polyhedral particles existing in a particle size range of 5 to 50 μm in one embodiment of the aluminum nitride powder of the present invention. [ Figure 2 ] is an explanatory diagram of the definition of the flat surface of particles having a particle size of 5 to 50 μm contained in the aluminum nitride powder of the present invention. DETAILED DESCRIPTION
[0014] Hereinafter, an example of an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiment described below, and any modifications can be made without departing from the gist of the present invention.
[0015] [Aluminum nitride powder] The aluminum nitride powder of the present invention is characterized in that (i) in the volume-based particle size distribution measured by particle size distribution measurement, the proportion of particles in the range of 5 to 150 μm in all particles is 60% by volume or more, (ii) In the frequency distribution curve obtained by the particle size distribution measurement, there are peaks in the particle size range of 5 to 50 μm (M range) and the particle size range of more than 50 μm and 150 μm or less (L range), and the proportion of particles in the M range (M range) is int ) and the ratio of particles in the L range (L int ) ratio (M int / L int ) is 0.2~1.0, In a scanning electron microscope image taken at a magnification of 500 times, 50% or more of particles having a particle size of 5 to 50 μm are polyhedral particles having at least two flat surfaces.
[0016] The aluminum nitride powder of the present invention is characterized in that, in a volume-based particle size distribution determined by a particle size distribution measurement, the proportion of particles in the range of 5 to 150 μm in all particles is 60 volume % or more. If the particles existing in the above-mentioned particle size range are less than 60 volume %, the filling rate of aluminum nitride to the resin is low, and the thermal conductivity of the resin composition containing the aluminum nitride powder is low. In the present invention, in order to further improve the thermal conductivity when forming the resin composition, the proportion of the particles in the range of 5 to 150 μm is preferably 62 volume % or more, more preferably 64 volume % or more, and even more preferably 66 volume % or more. In this specification, the average particle size of the aluminum nitride powder refers to the particle size (D 50 ).
[0017] The aluminum nitride powder of the present invention is characterized in that, in a frequency distribution curve obtained by particle size distribution measurement, the vertical axis represents the frequency fraction and the horizontal axis represents the particle size, peaks are present in a particle size range of 5 to 50 μm (M range) and a particle size range of more than 50 μm and 150 μm or less (L range), and the proportion of particles in the M range (M range) is 1.5-2.0. int ) and the ratio of particles in the above L range (L int ) ratio (M int / L int ) is 0.2 to 1.0. The ratio (M int / L int ) is less than 0.2, the fluidity decreases. On the other hand, the ratio (M int / L int ) exceeds 1.0, the thermal conductivity of the aluminum nitride in the resin composition decreases. In order to further improve the thermal conductivity and fluidity when forming the resin composition, the above ratio (M int / L int)Preferably, it is 0.3 to 0.9, more preferably 0.35 to 0.85, and still more preferably 0.4 to 0.8. It should be noted that in the present invention, the particle size distribution and frequency distribution curve are measured by the laser diffraction scattering method.
[0018] The shape of the aluminum nitride particles belonging to the L range is not particularly limited, and amorphous, spherical and other known-shaped aluminum nitride particles can be used without particular limitation. That is, the radius of curvature of the particle surface of the above-mentioned particles with a large particle size is large, and it effectively plays a role in the face contact with the polyhedral-shaped aluminum nitride particles belonging to the M range described later. In addition, as the shape of the aluminum nitride particles belonging to the L range, the polyhedral-shaped aluminum nitride particles detailed for the aluminum nitride powder belonging to the M range can be used. The aluminum nitride particles corresponding to the above L range, with a particle size exceeding 50 μm and 150 μm or less as measured by observation with a scanning electron microscope at a magnification of 500 times, are preferably aluminum nitride particles with an aspect ratio (the ratio of the major axis (L) to the minor axis (D), L / D) of 1 to 1.5 from the viewpoint of fluidity. The above aspect ratio is more preferably 1 to 1.4, and still more preferably 1 to 1.3.
[0019] As described above, the above aspect ratio is a value obtained by observing the aluminum nitride particles with a particle size exceeding 50 μm and 150 μm or less in the aluminum nitride powder by scanning electron microscope observation at a magnification of 500 times. The major axis (L) is defined as the maximum distance between any two points on the outer periphery of the aluminum nitride particle. The minor axis (D) is a line segment perpendicular to the major axis (L), and is defined as the line segment passing through the midpoint of the major axis (L) and two points on the outer periphery of the aluminum nitride particle. The average value of the ratio (L / D) of the major axis (L) to the minor axis (D) is calculated by measuring the ratio (L / D) of at least 20 or more aluminum nitride powder particles belonging to the L range and calculating their average value. Here, the aluminum nitride particles with a particle size determined by the scanning electron microscope image belonging to the range exceeding 50 μm and 150 μm or less refer to the aluminum nitride particles with a major axis (L) in the range exceeding 50 μm and 150 μm or less in the image of the aluminum nitride powder of the present invention observed by scanning electron microscope.
[0020] <Particles in the M range> In the present invention, it is characterized in that in the scanning electron microscope image taken at a magnification of 500 times, more than 50% of the particles with the above particle size belonging to the range of 5 to 50 μm are polyhedral particles having at least two flat surfaces. The ratio of polyhedral particles having a particle size of 5 to 50 μm in the aluminum nitride powder of the present invention is the ratio of the total area of the polyhedral particles to the total area of all aluminum nitride particles having a particle size of 5 to 50 μm determined in the scanning electron microscope image. Here, the aluminum nitride particles having a particle size of 5 to 50 μm as determined by a scanning electron microscope image refer to aluminum nitride particles having a major axis (L) of 5 to 50 μm in an image of the aluminum nitride powder of the present invention observed by a scanning electron microscope.
[0021] Figure 1 The scanning electron microscope image photographed at a magnification of 500 times is shown in one embodiment of the aluminum nitride powder of the present invention, which is polyhedral particles existing in a particle size range of 5 to 50 μm. The polyhedral particle 11 has a polyhedral shape with a plurality of flat surfaces a randomly present, and is an aluminum nitride particle having at least two flat surfaces a. The polyhedral particle 12 is also an aluminum nitride particle having at least two flat surfaces a. Figure 1 In addition to the polyhedral particle 11 and the polyhedral particle 12, there are a plurality of polyhedral particles.
[0022] The flat surface a of the multifaceted particles is different from the crushed surface formed by crushing aluminum nitride. Figure 1 As shown, it is a smooth flat surface without continuous concavo-convex structure and undulation. In the present invention, the term "flat surface" refers to a smooth, flat surface. As suitable aluminum nitride having such a flat surface, for example, aluminum nitride having a flat surface from the crystal growth surface of aluminum nitride can be cited, and the aluminum nitride has a smoother, flatter smooth surface from the crystal growth surface. In contrast, the crushed surface is inferior in flatness to the flat surface, and a large concavo-convex structure or undulation resulting from the crushing is observed in the scanning electron microscope observation, so it can be distinguished from the flat surface of the present invention. In addition, the flatter the flat surface a is, the better the smoother it is. For example, as described in more detail in the embodiment, in a 2000-fold SEM image of the cut surface of the particle, in arbitrarily selected 10 particles, the maximum value of the vertical distance between the contour line corresponding to the flat surface and the straight line connecting the ends of the contour line is set to M, and among the M values measured for the 10 selected particles, the maximum value M is max The average value M of M of 10 particles is preferably 0.3 μm or less, and more preferably 0.2 μm or less. A More preferably, it is 0.15 μm or less. Incidentally, the crushed surface generated by crushing the aluminum nitride block is smooth. max Including the concave and convex and convex not less than 0.3μm, in addition, the average value of the above maximum value MA Not less than 0.15μm. Above Figure 1 The polyhedral particles shown fully satisfy the above-mentioned properties. As the aluminum nitride particles having at least two flat surfaces a, known particles can be used without particular limitation, for example, polyhedral particles described in International Publication No. 2017 / 131239, etc., and particles having the flat surface a derived from the crystal growth surface of aluminum nitride are particularly preferred.
[0023] In the present invention, since more than 50% of the particles with a particle size of 5 to 50 μm are polyhedral particles, the thermal conductivity of the resin composition when filled in the resin is improved. Although the reason is uncertain, it is believed that since more than 50% of the polyhedral particles with multiple flat surfaces exist in the particle size range of 5 to 50 μm, the contact area between the particles is increased in the combination with the particles in the particle size range of more than 50 μm and less than 150 μm in the resin, and a heat conduction path is easily formed. In addition, by making the above-mentioned particles with a particle size of 5 to 50 μm have flat surfaces, the fluidity of the particles is improved, which can help improve the filling property when filling in the resin.
[0024] Preferably more than 55%, more preferably more than 60%, further preferably more than 65%, further preferably more than 70%, and particularly preferably more than 80% of the particles with a particle size of 5 to 50 μm are polyhedral particles having at least two flat surfaces, in which case the above-mentioned effect can be further obtained.
[0025] As described above, the flat surface possessed by multifaceted particles is different from the broken surface with bumps or undulations on the surface. In the particle size range of 5 to 50 μm, when the number of particles with broken surfaces is small and the multifaceted particles exist in a certain proportion or more, the fluidity of the resin composition filled in the resin tends to improve. Without being limited by a specific theory, it is believed that when the proportion of particles with broken surfaces is small and the multifaceted particles exist in a certain proportion or more, particles with a particle size of more than 50 μm and less than 150 μm, particles with a particle size in the range of 5 to 50 μm, etc. roll on the smooth and flat surface of the multifaceted particles, and the resistance to flow is suppressed as a whole, so the fluidity tends to improve. On the other hand, it is believed that when the proportion of particles with broken surfaces is large, it becomes a resistance to rolling, so the fluidity decreases. As can be seen from the above, by providing the particles having a particle size of 5 to 50 μm with the above characteristics, the aluminum nitride powder of the present invention can achieve both improved thermal conductivity and good fluidity when filled in a resin to form a resin composition.
[0026] For the above reasons, the proportion of particles having crushed surfaces in the aluminum nitride powder of the present invention is preferably 20% or less, more preferably 10% or less. The abundance ratio of particles having broken surfaces is the ratio of the total area of particles having broken surfaces to the total area of all aluminum nitride particles identified in an image observed with a scanning electron microscope at a magnification of 500 times.
[0027] The number of flat surfaces possessed by the multifaceted particles is not particularly limited as long as it is 2 or more. However, from the viewpoint of increasing the contact area between particles when filled into the resin, it is preferably 3 or more. In addition, the upper limit of the flat surfaces possessed by the multifaceted particles is not particularly limited, for example, 10. In addition, two continuous flat surfaces are preferably continuous in a manner to form a hilly portion. The number of flat surfaces of the polyhedral particles was determined based on an image observed with a scanning electron microscope (SEM) at a magnification of 500 times.
[0028] From the viewpoint of increasing the contact area between particles when filled in resin to improve thermal conductivity, the area of each flat surface of the multifaceted particle is preferably large to a certain extent. From such a viewpoint, the multifaceted particle preferably has at least two flat surfaces with an area of 2 to 1600 μm. 2 More preferably, at least three flat surfaces with an area of 2 to 1600 μm 2 flat surface. The area of the flat surface was determined from an image observed with a scanning electron microscope (SEM) at a magnification of 500 times.
[0029] The average value of the ratio (L / D) of the major diameter (L) to the minor diameter (D) of the aluminum nitride particles in the particle size range of 5 to 50 μm is preferably 1 to 1.4, more preferably 1 to 1.3, and further preferably 1.0 to 1.2. If the above ratio (L / D) is within the above range, the fluidity of the resin composition formed by filling the aluminum nitride powder into the resin can be well maintained, so the workability is more excellent. The major axis (L) and minor axis (D) of particles within the above-mentioned particle size range of 5 to 50 μm can be determined by observing aluminum nitride particles with a particle size of 5 to 50 μm in the aluminum nitride powder at a magnification of 500 times using a scanning electron microscope. The major diameter (L) is defined as the maximum distance between any two points on the periphery of the aluminum nitride particle. The minor diameter (D) is a line segment perpendicular to the major diameter (L) and is defined as a line segment passing through the midpoint of the major diameter (L) and two points on the periphery of the aluminum nitride particle. The average value of the ratio (L / D) of the major axis (L) to the minor axis (D) is calculated by measuring the ratio (L / D) of at least 20 aluminum nitride particle powders falling within the above particle size range and calculating their average value. The aluminum nitride particles including the polyhedral particles and having a particle size within the range of 5 to 50 μm can be obtained, for example, by the production method described below.
[0030] The oxygen content of the particles in the aluminum nitride powder of the present invention falling within the range M is preferably 0.5 mass % or less, because this imparts high thermal conductivity to the particles themselves. Here, the oxygen content is the total oxygen content measured by the high temperature thermal decomposition method described in the Examples. When the oxygen content is 0.5 mass % or less, the particles falling within the M range can maintain high thermal conductivity, and the resin composition containing the aluminum nitride powder also has high heat dissipation properties. The oxygen content is more preferably 0.4 mass % or less, further preferably 0.3 mass % or less, and further preferably 0.2 mass % or less.
[0031] The aluminum nitride powder of the present invention preferably further contains particles having a particle size of less than 5 μm (S range) (hereinafter sometimes referred to as "small particles"). By containing particles in the S range, the fluidity of the resin composition can be further improved. The reason why the fluidity of the aluminum nitride powder as a whole is improved by further including particles in the S range is not yet clear, but is presumed as follows: That is, by filling the spaces between the aluminum nitride particles having a particle size range of the L range and the aluminum nitride particles having a particle size range of the M range with these small particles, the resin component contributing to fluidity is relatively increased, and the fluidity as a whole is further improved. As described above, the particle size of the small particles having a peak in the S range is 4.5 μm or less, more preferably 4 μm or less, further preferably 3.5 μm or less, and further preferably 3 μm or less. The lower limit of the particle size of the small particles is not particularly limited, but is preferably 0.05 μm, more preferably 0.1 μm, and further preferably 0.15 μm. A part or all of the small particles may be made of a material other than aluminum nitride, such as aluminum oxide.
[0032] The above-mentioned small particles that can be included in the aluminum nitride powder of the present invention are not particularly limited. For example, they can be aluminum nitride particles having the particle size, or can be particles such as aluminum oxide particles, calcium oxide particles, yttrium oxide, zinc oxide, silicon dioxide, and silicon nitride. Among them, the small particles are preferably aluminum nitride particles and / or aluminum oxide particles.
[0033] The content of the above-mentioned small particles in the aluminum nitride powder is not particularly limited as long as it is less than 40% by volume, but is preferably 35% by volume or less, and more preferably 30% by volume or less. By making the amount of the small particles within the above range, the thermal conductivity of the resin composition when the aluminum nitride powder is filled in the resin can be maintained at a high level, and extremely good fluidity can be achieved.
[0034] [Method for producing aluminum nitride powder] The method for producing the aluminum nitride powder of the present invention is not particularly limited as long as the aluminum nitride powder having the following characteristics can be obtained. (i) in the volume-based particle size distribution measured by particle size distribution measurement, the proportion of particles in the range of 5 to 150 μm in all particles is 60% by volume or more, (ii) In the frequency distribution curve obtained by the particle size distribution measurement, there are peaks in the particle size range of 5 to 50 μm (M range) and the particle size range of more than 50 μm and 150 μm or less (L range), and the proportion of particles in the M range (M range) is int ) and the ratio of particles in the L range (L int ) ratio (M int / L int ) is 0.2~1.0, In a scanning electron microscope image taken at a magnification of 500 times, 50% or more of particles having a particle size of 5 to 50 μm are polyhedral particles having at least two flat surfaces. For example, by mixing aluminum nitride powder having a peak in the above-mentioned L range and aluminum nitride powder having a peak in the M range and containing polyhedral particles with a particle size of 5 to 50 μm, the ratio (M) after mixing is adjusted to int / L int ) satisfies the above range, the aluminum nitride powder of the present invention can be obtained. When mixing, the above small particles can be mixed.
[0035] The aluminum nitride powder falling within each average particle size range may be any commonly used aluminum nitride powder without particular limitation as long as it has a predetermined average particle size. For example, the aluminum nitride powder may be one produced by a reduction nitridation method, or one produced by a direct nitridation method such as a combustion synthesis method and adjusted to a predetermined average particle size through a pulverization and classification process, or one produced by a production method other than these.
[0036] As an example of a method for producing an aluminum nitride powder having a peak in the M range in the frequency distribution curve and in which particles in the 5 to 50 μm range include polyhedral particles, there can be mentioned a production method including the following steps 1 and 2. Step 1: average particle size 0.5 to 5 μm, specific surface area 1.2 to 16.0 m 2 100 parts by mass of the first aluminum nitride powder raw material having an average particle size of 3 to 40 μm and a specific surface area of 0.05 to 1.8 m 2 / g and a ratio (SA2 / SA1) of the specific surface area (SA2) of the first aluminum nitride powder raw material to the specific surface area (SA1) of the first aluminum nitride powder raw material is 0.8 or less to prepare a raw material mixture. Step 2: A step of heating the raw material mixture to 1750° C. to 2100° C. under supply of an inert gas.
[0037] <Process 1> Step 1 is to prepare a particle with an average particle size of 0.5 to 5 μm and a specific surface area of 1.2 to 16.0 m 2 100 parts by mass of the first aluminum nitride powder raw material having an average particle size of 3 to 40 μm and a specific surface area of 0.05 to 1.8 m 2 / g, and a ratio (SA2 / SA1) of the specific surface area (SA2) of the second aluminum nitride powder raw material to the specific surface area (SA1) of the first aluminum nitride powder raw material is less than 0.8 to prepare a raw material mixture. The raw material mixture contains aluminum nitride having different average particle sizes in predetermined amounts, and is subjected to a heating step (step 2) described below, thereby obtaining aluminum nitride powder containing polyhedral particles having at least two flat surfaces. The specific surface area of each raw material powder is determined by the BET method using N 2 adsorption, for example, using a flow-type surface area automatic measuring device FlowSorb 2300 model manufactured by Shimadzu Corporation.
[0038] That is, it is believed that by the presence of an appropriate amount of the second aluminum nitride powder raw material having a relatively large average particle size, the first aluminum nitride powder raw material having a small average particle size enters the second aluminum nitride powder raw material through a sublimation reaction during the heating process, and the second aluminum nitride powder raw material crystallizes and grows, and the particle size becomes larger. It is also presumed that the polyhedral particles specified above are formed through such crystal growth. It is further presumed that since the oxygen present in the first aluminum nitride powder can be effectively removed through the above-mentioned sublimation reaction, the oxygen content of the polyhedral particles of aluminum nitride produced through the heating process becomes low. As described above, by using the first and second aluminum nitride powder raw materials in combination in predetermined blending amounts, the above-mentioned crystal growth can be sufficiently performed, and aggregation between particles can be suppressed.
[0039] The first aluminum nitride powder raw material has an average particle size of 0.5 to 5 μm and a specific surface area of 1.2 to 16.0 m 2 / g, preferably with an average particle size of 0.7 to 5 μm and a specific surface area of 1.2 to 12.0 m 2 / g. The average particle size of the second aluminum nitride powder raw material is 3 to 40 μm, and the specific surface area is 0.05 to 1.8 m 2 The average particle size of the second aluminum nitride powder raw material can be appropriately selected depending on the target average particle size, and is preferably 3 to 20 μm, and more preferably 5 to 15 μm. The amount of the second aluminum nitride powder raw material in the raw material mixture relative to 100 parts by mass of the first aluminum nitride powder raw material is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and even more preferably 3 to 10 parts by mass. As described above, by appropriately adjusting the amounts of the first and second aluminum nitride powder raw materials, it is easy to obtain an aluminum nitride powder having an average particle size of 5 to 50 μm (having a peak in the M range in the frequency distribution curve) and containing polyhedral particles.
[0040] The ratio (SA2 / SA1) of the specific surface area (SA2) of the second aluminum nitride powder raw material to the specific surface area (SA1) of the first aluminum nitride powder raw material is preferably 0.8 or less. By adjusting the specific surface area ratio (SA2 / SA1), a resin composition with higher thermal conductivity can be obtained. Without being bound by a specific theory, it is believed that by setting the above-mentioned specific surface area ratio, more forms of particles with a particle size of 5 to 50 μm can become polyhedral particles, so as described above, the contact area between particles when filling the resin composition is increased, and a heat conduction path is easily formed. The above-mentioned specific surface area ratio (SA2 / SA1) is more preferably less than 0.7, and further preferably less than 0.6. It should be noted that the lower limit of the specific surface area ratio (SA2 / SA1) is not particularly limited, for example, 0.005.
[0041] The raw material mixture may contain an additive for liquid phase formation and / or an additive for promoting particle growth during sintering. As additives, oxides of alkali metals, alkaline earth metals or rare earth elements are generally known, and yttrium oxide is a representative example. The content of the additive in the raw material mixture is preferably about 1 to 10% by mass on a mass basis.
[0042] As long as the first and second aluminum nitride powder raw materials have a predetermined average particle size, commonly used aluminum nitride powder raw materials can be used without particular limitation. For example, aluminum nitride powder produced by a reduction nitridation method, aluminum nitride powder produced by a direct nitridation method such as a combustion synthesis method and adjusted to a predetermined average particle size through a crushing and classification process, or aluminum nitride powder produced by a production method other than these. Among them, since crushing and classification processes are not required, the first and second aluminum nitride powder raw materials are preferably produced by a reduction nitridation method. It is preferred that the aluminum nitride powder produced through step 1 and step 2 be used as a second aluminum nitride powder raw material, and step 1 and step 2 be performed again, thereby obtaining an aluminum nitride powder having a larger average particle size.
[0043] <Process 2> Step 2 is a step of heating the raw material mixture prepared in step 1 to 1750 to 2100° C. under supply of an inert gas. By setting the heating temperature to 1750°C or higher, the crystal growth of aluminum nitride particles is promoted, and aluminum nitride powder containing aluminum nitride particles having a smooth flat surface (smooth surface) is easily obtained. On the other hand, by setting the heating temperature to 2100°C or lower, agglomeration caused by fusion bonding between particles can be suppressed. From this point of view, the heating temperature is preferably 1750 to 2100°C, more preferably 1800 to 2050°C, and even more preferably 1800 to 2000°C. In addition, the heating time is not particularly limited, but is preferably 1 to 20 hours, and more preferably 2 to 15 hours. As long as the heating time is 1 hour or more, the crystal growth of the aluminum nitride particles is fully carried out, and a smooth flat surface is easily formed. On the other hand, even if the heating exceeds 20 hours, the particle growth is difficult to continue, which is disadvantageous in industrial implementation.
[0044] The heating is performed under the supply of an inert gas. That is, it is most preferred to supply an inert gas to a heating device for accommodating the raw material mixture and heating the raw material mixture, but the heating can also be performed while continuously supplying the inert gas. In addition, the raw material mixture is filled in a heating container (hereinafter also referred to as a "container") and placed in the above-mentioned heating device. As the above-mentioned container, a carbon container is preferably used. As the inert gas, argon gas and nitrogen gas can be used, preferably nitrogen gas.
[0045] <Other Processes> After step 2, a crushing step may be performed as needed. The crushing step is performed to break the bonds between loosely bonded aluminum nitride particles, and is different from the pulverization step in which the aluminum nitride particles are partially crushed. Therefore, even if the crushing step is performed, the shape of the polyhedral particles can be maintained, and particles with broken surfaces are hardly generated. The crushing can be carried out by a known method, for example, by a roll crusher, a jet mill, a ball mill, a mass crusher, a jaw crusher, or the like.
[0046] Alternatively, an oxidation step may be performed after step 2, and the oxidation step is preferably performed after the above-mentioned crushing step. By performing the oxidation step, decomposition due to contact with water or the like can be prevented. The oxidation step can be performed by heating in an air atmosphere. The heating temperature in the oxidation step is not particularly limited, but is preferably 500 to 900° C., more preferably 600 to 800° C. The heating time is not particularly limited, but is preferably 1 to 20 hours, more preferably 5 to 15 hours. The oxygen content of the oxide film formed in the oxidation step is included in the oxygen content of the aluminum nitride powder. By performing the oxidation step so that the oxygen content is within the range of the oxygen content of the aluminum nitride powder, excellent thermal conductivity can be imparted to the obtained resin composition when filled into a resin.
[0047] In order to improve compatibility with resins, water resistance, etc., the aluminum nitride powder of the present invention can be subjected to surface treatment as required. As surface treatment, known methods can be applied. For example, silicone oil, silylating agent, silane coupling agent and other organic silicon compounds, phosphoric acid, phosphate, fatty acid and other acids, polyamide resin and other polymer compounds, aluminum oxide, silicon dioxide and other inorganic substances can be used for surface treatment.
[0048] <Purpose> The use of the aluminum nitride powder of the present invention is not particularly limited, and it can be used as a raw material for an aluminum nitride substrate, preferably for resin filling. The aluminum nitride powder of the present invention is preferably filled into a resin and used as a resin composition containing a resin and aluminum nitride powder. As described above, the aluminum nitride powder of the present invention contains particles having a particle size in a specific range at a specific volume ratio, and more than 50% of the particles in the specific range are polyhedral particles having at least 2 flat surfaces, so when filled into a resin to form a resin composition, the thermal conductivity is high and the fluidity is good. As described above, since the contact area between the particles in the aluminum nitride powder is large, it is easy to effectively form a heat conduction path in the resin composition, and it can be suitable for use as a heat dissipation component (heat dissipation material).
[0049] The resin contained in the resin composition is not particularly limited, and examples thereof include: epoxy resin, epoxy resin with mesogen group introduced, unsaturated polyester resin, polyimide resin, phenolic resin and other thermosetting resins, polyethylene, polypropylene, polyamide, polycarbonate, polyphenylene sulfide and other thermoplastic resins, ethylene propylene rubber, styrene butadiene rubber and other rubbers, silicone resins and the like. Among them, epoxy resins and silicone resins are preferred.
[0050] The content of the aluminum nitride powder of the present invention contained in the resin composition is not particularly limited, but is preferably 300 to 5000 parts by mass, more preferably 400 to 5000 parts by mass, relative to 100 parts by mass of the resin. When the content of the aluminum nitride powder is above these lower limits, the thermal conductivity of the resin composition is improved, and when the content of the aluminum nitride powder is below these upper limits, the fluidity of the resin composition is improved, and the handling properties such as moldability are improved.
[0051] The resin composition may contain fillers other than the aluminum nitride powder of the present invention within a range not inhibiting the effects of the present invention. Examples of other fillers include aluminum oxide, zinc oxide, boron nitride, silicon nitride, silicon carbide, graphite, and the like, in addition to aluminum nitride powder that does not satisfy the conditions of the present invention. The mixing ratio of the aluminum nitride powder of the present invention and other fillers can be appropriately adjusted within the range of 1:99 to 99:1.
[0052] The resin composition may contain additives such as a plasticizer, a vulcanizing agent, a curing accelerator, and a release agent as necessary.
[0053] The resin composition can be manufactured by mixing the components with a stirrer or a mixer. The resin composition thus obtained can be made into a heat dissipation component (heat dissipation material) of a desired form such as a heat sink or a heat dissipation paste by a known molding method. As molding methods, for example, extrusion molding, compression molding, a scraper method, a resin impregnation method, etc. can be cited, and as required, heat curing, light curing, etc. can be performed after molding. In one embodiment of the present invention, there is provided an electronic device including the heat dissipation member and an electronic device having a heat generating portion or a cooling portion, wherein the heat dissipation member is disposed on the electronic device so as to contact the heat generating portion. Example
[0054] Hereinafter, although an Example is shown in order to demonstrate this invention more concretely, this invention is not limited to these Examples.
[0055] [Measurement method] Various physical properties in Examples and Comparative Examples were measured by the following methods. (1) Particle size distribution measurement The particle size distribution is measured on a volume basis by dispersing aluminum nitride powder in a solution obtained by adding a 5% sodium pyrophosphate aqueous solution to 90 ml of water and dispersing the dispersed material with a homogenizer using a laser diffraction particle size distribution apparatus ("MICROTRAC HRA" manufactured by Microtrac BEL).
[0056] (2) The proportion of particles in the M range (M int ) and the particle ratio in the L range (L int ) ratio (M int / L int ) The particle size distribution of aluminum nitride powder was measured by the method (1) above, and a frequency distribution curve with the vertical axis being the frequency distribution and the horizontal axis being the particle size was obtained based on the measured data. When there were peaks in the particle size range of 5 to 50 μm (M range) and the particle size range of more than 50 μm and less than 150 μm (L range), the particle ratio (M range) in the M range was obtained. int ) and the particle ratio (L int ) ratio (Mint / L int ).
[0057] (3) The presence and proportion of polyhedral particles Regarding the aluminum nitride powder, a scanning electron microscope ("TM3030" manufactured by Hitachi High-Technologies Corporation) was used to take a SEM photograph at a magnification of 500 times (accelerating voltage 15 kV, secondary electron detection). From the SEM photograph, it was confirmed whether there were particles with two or more flat surfaces in the aluminum nitride powder belonging to the M range in the above-mentioned frequency distribution curve, and whether there were polyhedral particles. The number of fields of view of the SEM photograph was 10 or more. The abundance ratio of polyhedral particles is calculated by calculating the ratio of the total area of polyhedral particles to the total area of all aluminum nitride particles having a particle size of 5 to 50 μm obtained by image analysis of the SEM photograph, and this is taken as the abundance ratio of polyhedral particles. Specifically, it is calculated by the following formula. The existence ratio of polyhedral particles (%) = [(total area of polyhedral particles) / (total area of all aluminum nitride particles with a particle size in the range of 5 to 50 μm)] × 100
[0058] (4) Evaluation of flat surface Aluminum nitride powder is filled into acrylic resin, and after curing, it is cut at an arbitrary position. In the 2000-fold SEM image of the cut surface, any 10 particles with flat surfaces are selected. Figure 2 As shown, a straight line L is drawn connecting the end P1 and the end P2 of the contour line forming the flat surface, and the maximum value of the perpendicular distance between the straight line L and the contour line is set as M, and the maximum value of the values of M measured in the 10 particles selected above is set as M. max。 In addition, the average value of the above M is represented as M A .
[0059] (5) Ratio of the particle's major diameter (L) to minor diameter (D) (L / D) Regarding the aluminum nitride powder, a scanning electron microscope ("TM3030" manufactured by Hitachi High-Technologies Corporation) was used to take a SEM photograph at a magnification of 500 times (accelerating voltage 15 kV, secondary electron detection). From the obtained SEM photograph, the ratio of the major diameter (L) to the minor diameter (D) of the aluminum nitride particles with a particle size in the above-mentioned specific range was obtained, and their average value was calculated as the ratio (L / D) of the major diameter (L) to the minor diameter (D) of the particles.
[0060] (6) Oxygen content The oxygen content of the aluminum nitride powder was measured using an oxygen / nitrogen analyzer "EMGA-620W" manufactured by Horiba, Ltd., from the amount of CO gas generated by a high-temperature thermal decomposition method in a graphite crucible to measure the oxygen content (oxygen concentration) contained in the aluminum nitride powder. The oxygen concentration of the powder belonging to the M range in the frequency distribution curve is measured by separating aluminum nitride powder having a particle size corresponding to the above range with a sieve.
[0061] (7) Thermal conductivity of resin composition Aluminum nitride powder and silicone resin were mixed to obtain a resin composition. The resin composition was hot-pressed at 100° C. to obtain a sheet with a thickness of 7 mm. The thermal conductivity of the obtained sheet was measured using a hot plate method thermal property measuring device (manufactured by Kyoto Electronics Co., Ltd., TPS500).
[0062] (8) Flowability of resin composition The resin composition obtained in the above (7) was measured for its discharge amount per minute (g / min) using a syringe "PSY-30F" manufactured by Musashi Engineering Co., Ltd. The inner diameter of the main body of the storage syringe sample was 22 mm, and the inner diameter of the tip portion of the sample discharge was 2 mm. The discharge pressure was 0.62 Pa.
[0063] [Raw materials used] The following ingredients were used. In the frequency distribution curve, aluminum nitride raw materials have a peak in the L range Aluminum nitride powder (L-AlN) having an average particle size of 120 μm prepared by a reduction nitridation method (hereinafter referred to as “particles belonging to the L range” or “L range particles” in the examples) In the frequency distribution curve, aluminum nitride raw materials have a peak in the M range Aluminum nitride powder obtained by the following synthesis method (hereinafter referred to as "particles belonging to the M range" or "M range particles" in the examples) Small particles (S-1) with a peak in the S range in the frequency distribution curve Aluminum nitride powder with an average particle size of 1 μm (hereinafter referred to as "particles belonging to the S range (S-1)" or "S range particles (S-1)" in the examples) Small particles (S-2) with a peak in the S range in the frequency distribution curve Alumina having an average particle size of 0.3 μm (hereinafter referred to as “particles belonging to the S range (S-2)” or “S range particles (S-2)” in the examples)
[0064] (Synthesis example 1) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 7.8 μm and a specific surface area of 0.62 m 210 parts by mass of aluminum nitride powder raw materials with a concentration of 100 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 2000°C for 5 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 18.7 μm and a specific surface area of 0.20 m 2 / g of aluminum nitride powder (M-AlN1). The oxygen content of the obtained M-AlN1 was 0.14 mass%. max 0.17μm, M A 0.05μm.
[0065] (Synthesis example 2) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 16.2 μm, specific surface area 0.23 m 2 5 parts by mass of a raw material of aluminum nitride powder having a value of / g and 0.1 parts by mass of calcium fluoride as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1900°C for 18 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 26.3 μm and a specific surface area of 0.19 m 2 / g aluminum nitride powder (M-AlN2). The oxygen content of the obtained M-AlN2 was 0.11% by mass. max 0.16μm, M A It is 0.07μm.
[0066] Example 1 The ratio of the aluminum nitride raw material (L-AlN) belonging to the L range to the aluminum nitride raw material (M-AlN1) belonging to the M range (M-AlN1) is calculated. int / L int ) were mixed into the values shown in Table 1 to prepare aluminum nitride powder. The obtained aluminum nitride powder and silicone resin were stirred with a blade type stirrer to prepare a resin composition. Specifically, as the above-mentioned resin, a mixture of a platinum catalyst (1,2-divinyltetramethyldisiloxane complex of platinum) with a concentration of 20 ppm converted to platinum element and 300 ppm of 1-ethynyl-1-cyclohexanol (viscosity (25°C): 100 mPa·s) and decyltrimethoxysilane is added to a mixture obtained by mixing a vinyl silicone with two ends and a polysiloxane having a hydrosilyl group in a mass ratio of 97:3, thereby preparing a base resin. Next, the base resin and the aluminum nitride powder were mixed using a blade type mixer so that the filling rate of the aluminum nitride powder was 75 volume %, thereby preparing a resin composition. The thermal conductivity and fluidity of the obtained resin composition were measured.
[0067] Example 2 Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 1 except that particles (S-1) belonging to the S range were used, the filling rate of the aluminum nitride powder was 82% by volume, and the mixing ratio was changed as shown in Table 1. The results of measuring the thermal conductivity and fluidity of the obtained resin composition are shown in Table 1.
[0068] Example 3 As the aluminum nitride raw material belonging to the M range, M-AlN2 was used, and particles (S-1) and (S-2) belonging to the S range were used in a ratio such that the ratio of (S-2) in the S range particles was 50 volume %, and the mixing ratio was changed as shown in Table 1. In the same manner as in Example 1, an aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained. The results of measuring the thermal conductivity and fluidity of the obtained resin composition are shown in Table 1.
[0069] Example 4 As the aluminum nitride raw material belonging to the M range, M-AlN1 was used, and the ratio of L range particles and the ratio of M range particles were changed to the ratios shown in Table 1 so that M int / L int Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 3 except that the ratio was set to the ratio shown in Table 1. Table 1 shows the measurement results of the thermal conductivity and fluidity of the obtained resin composition.
[0070] Example 5 The ratio of L range particles and the ratio of M range particles were changed to the ratios shown in Table 1 so that M int / L int Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 2 except that the ratio was as shown in Table 1. Table 1 shows the measurement results of the thermal conductivity and fluidity of the obtained resin composition.
[0071] Comparative Example 1 Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 1 except that a commercially available aluminum nitride powder having substantially no flat surface was used as the aluminum nitride powder constituting the range M. The results of measuring the thermal conductivity and fluidity of the obtained resin composition are shown in Table 1.
[0072] Comparative Example 2 The ratio of L range particles and the ratio of M range particles were changed to the ratios shown in Table 1 so that M int / L int Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 1 except that the ratio was as shown in Table 1. Table 1 shows the measurement results of the thermal conductivity and fluidity of the obtained resin composition.
[0073] Comparative Example 3 The ratio of L range particles and the ratio of M range particles were changed to the ratios shown in Table 1 so that M int / L int Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 1 except that the ratio was as shown in Table 1. Table 1 shows the measurement results of the thermal conductivity and fluidity of the obtained resin composition.
[0074] Comparative Examples 4 to 5 The ratio of L range particles and the ratio of M range particles were changed to the ratios shown in Table 1 so that M int / L int Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 2 except that the ratio was as shown in Table 1. Table 1 shows the measurement results of the thermal conductivity and fluidity of the obtained resin composition.
[0075] Comparative Example 6 The ratio of L range particles and the ratio of M range particles were changed to the ratios shown in Table 1 so that M int / L int Aluminum nitride powder and a resin composition containing the aluminum nitride powder were obtained in the same manner as in Example 2 except that the ratio was changed to the ratio shown in Table 1 and the ratio of the S range particles was changed to the ratio shown in Table 1. The results of measuring the thermal conductivity and fluidity of the obtained resin composition are shown in Table 1.
[0076]
[0077] From the above results, it can be seen that by making more than 50% of the aluminum nitride powder particles with a particle size of 5 to 50 μm contained in the resin composition of each embodiment multi-faceted particles, the thermal conductivity of the resin composition when filled in the resin is improved, and by making the particles with a particle size of 5 to 50 μm have flat surfaces, the fluidity of the particles is also excellent. Description of Reference Numerals
[0078] 11, 12 Polyhedral particles a Flat surface
Claims
1. An aluminum nitride powder, wherein: (i) in the volume-based particle size distribution measured by particle size distribution measurement, the proportion of particles in the range of 5 to 150 μm in all particles is 60% by volume or more, (ii) In the frequency distribution curve obtained by the particle size distribution measurement, there are peaks in the particle size range of 5 to 50 μm, i.e., the M range, and the particle size range of more than 50 μm and 150 μm or less, i.e., the L range, respectively. The proportion of particles in the M range is int The ratio of particles in the L range is L int Ratio M int / L int 0.2~1.0, In a scanning electron microscope image taken at a magnification of 500 times, 50% or more of particles having a particle size of 5 to 50 μm are polyhedral particles having at least two flat surfaces.
2. The aluminum nitride powder according to claim 1, further comprising particles having a particle size of less than 5 μm, i.e., in the S range.
3. The aluminum nitride powder according to claim 2, wherein The particles having a particle size smaller than 5 μm, i.e., in the range of S, are aluminum nitride particles and / or aluminum oxide particles. 4 . A resin composition comprising the aluminum nitride powder according to claim 1 and a resin. 5 . A heat dissipation component comprising the resin composition according to claim 4 . 6 . An electronic device comprising the heat dissipation member according to claim 5 and an electronic device having a heat generating portion or a cooling portion, wherein the heat dissipation member is disposed on the electronic device so as to contact the heat generating portion.
Citation Information
Patent Citations
Aluminum nitride powder, production method therefor, and its use
JP2003119010A
Aluminum nitride particle
WO2017131239A1
Aluminum nitride-based powder and method for producing same
WO2018216591A1